2015
DOI: 10.1002/jor.22779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trypsinization and mineralization on intrasynovial tendon allograft healing to bone

Abstract: The purpose of the current study was to develop a novel technology to enhance tendon-to-bone interface healing by trypsinizing and mineralizing (TM) an intrasynovial tendon allograft in a rabbit bone tunnel model. Eight rabbit flexor digitorum profundus (FDP) tendons were used to optimize the trypsinization process. An additional 24 FDP tendons were stratified into control and TM groups; in each group, 4 tendons were used for in vitro evaluation of TM and 8 were transplanted into proximal tibial bone tunnels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A number of different methods exist to preserve, sterilise or decellularise tendon grafts. Freezing and cryopreservation [16, 39, 72, 74, 86, 95], irradiation [20, 22, 37, 40, 41, 87–89, 91], gas‐sterilisation [8], lyophilising [72] and other methods [17, 44, 80] have been described and tested for potential effects on material properties. These studies revealed that care must be taken to choose processing methods that do not or minimally compromise their biomechanical properties, which would be, of course, highly undesirable.…”
Section: Resultsmentioning
confidence: 99%
“…A number of different methods exist to preserve, sterilise or decellularise tendon grafts. Freezing and cryopreservation [16, 39, 72, 74, 86, 95], irradiation [20, 22, 37, 40, 41, 87–89, 91], gas‐sterilisation [8], lyophilising [72] and other methods [17, 44, 80] have been described and tested for potential effects on material properties. These studies revealed that care must be taken to choose processing methods that do not or minimally compromise their biomechanical properties, which would be, of course, highly undesirable.…”
Section: Resultsmentioning
confidence: 99%
“…Although transplantation of tendons has been associated with adverse effects [17], there were no obvious evidence of this in our study. Tendon-to-bone treatment is the most challenging method for reconstruction of cartilaginous tissues or bone healing [9]. A previous study [18] indicated that tendon–bone integration of allograft tendons was not achieved even 2 years after reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of tendons was conducted according to the method described in a previous study [9]. Briefly, immediately after sacrifice, the hind paws were harvested and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular migration can also be promoted by modification of artificial ligaments by growth factors [ 49 ] and bioactive proteins [ 50 ], which effectively improve bone tissue ingrowth to promote graft-to-bone healing [ 51 , 52 ]. In future studies, we should use an improved knitting method in combination with surface modification to increase the biocompatibility of the PET-ALs.…”
Section: Discussionmentioning
confidence: 99%